Edukasi Pencegahan Kecacingan Melalui Pendampingan Pembiasaan PHBS Pada Siswa SDN 2 Toronipa, Kabupaten Konawe - La Ode Muhamad Sety; Akifah Akifah; Renni Meliahsari; La Ode Liaumin Azim (FKM UIN Sumatera Utara Medan, 2025)
Helminthiasis are a group of parasitic worms that are transmitted to humans from one host to another through the soil. These cases are commonly found in preschool and elementary school children. The purpose of this community service activity is to educate students at SDN 2 Toronipa about clean and healthy living behaviors (PHBS) as an effort to prevent or reduce cases of helminthiasis in children. The activity involved dissemination through educational sessions, distribution of posters, handwashing demonstrations, and measurement of weight and height. The results showed that the students understood the educational material provided, resulting in an increase in knowledge before and after the education. The participants' response to the activity was very good and enthusiastic. Therefore, educational sessions are one of the ways to disseminate information or education to students about helminthiasis and PHBS.